Experimental study on self-acceleration in expanding spherical hydrogen-air flames. (5th July 2018) - Kim, Wookyung; Sato, Yoshitatsu; Johzaki, Tomoyuki; Endo, Takuma; Shimokuri, Daisuke; Miyoshi, Akira
Abstract: The development of cellularity for expanding spherical hydrogen-air flames at elevated pressure, owing to hydrodynamic and diffusional-thermal instabilities was experimentally investigated using high-speed schlieren images. The critical flame radii and critical Peclet numbers at which cracks begin to propagate and for the onset of flame acceleration were obtained. The dependency of Pe cl on Ma for hydrogen-air flames was compared with that for other fuels. The results showed that cellular development depends on the intensity of the diffusional-thermal instability. The acceleration exponent and fractal excess for the acceleration regime of a hydrogen-air flame were evaluated. The values show that the transition regime and self-similar regime exist in the acceleration regime of expanding spherical hydrogen-air flames. Highlights: We investigated the development of cellularity on expanding spherical propagation of hydrogen-air flames. The critical flame radii at which cracks begin to propagate and for the onset of flame acceleration were obtained. The acceleration exponent and fractal excess were evaluated. Results show that the transition regime and self-similar regime exist in the flame propagation.